Enhancing Teachers' Professional Development By Implementing Smart Apps Creator (SAC) - Aliva Rosdiana; Aan Widiyono; Nurul Nisah; Muhammad Najih Al Azizi; Lola Aulia Putri (KUAT : Keuangan Umum dan Akuntansi Terapan, 2024)
New paradigm of learning addresses the shift of how education and learning approaches in the modern era. Smart Apps Creator (SAC) constitutes a new digital-based application to assist teachers create an effective learning environment. As android-based learning media, SAC has a long-term memory to be stored without requiring coding expertise since it is easy to use by educators. This community service is aimed at enhancing teachers’ professional development in implementing smart apps creator (SAC) by providing teachers and stakeholders at SDN 2 Pekalongan Jepara knowledge and training of applying SAC. The activity method employed includes expository, Q&A, demonstration, and evaluation. The result of this activity after getting a post-test conducted to 22 teachers and stakeholders is that 81% teachers as participants claimed having enlightened ideas, knowledge and skill improved. Besides, the score average of post-test delivered was a higher score of 95 than the average of pretest scores of 48. Most teachers expected a sustainable training program as the follow-up of community service.